The role of repeat fine needle aspiration in managing indeterminate thyroid nodules - Allen, Laura (J Otolaryngol Head Neck Surg, 2019)
BACKGROUND: The Bethesda System is the most widely used for reporting fine needle aspiration (FNA) cytology. It recommends a repeat FNA (rFNA) when initial results are category I or III. It is unclear how often rFNA provides additional diagnostic information. We sought to investigate its utility at our institution. METHODS: A retrospective chart review was performed of patients who had a category I or III FNA result and underwent rFNA of the same thyroid nodule between 2013 and 2015 at the QE II Health Sciences Centre in Nova Scotia, Canada. Results of initial FNA and ultrasound characteristics, rFNA, demographic data, surgical details, and pathology were collected. RESULTS: A total of 237 patients (474 thyroid FNAs) were included. Most initial FNAs were category I (82%), the remainder category III (18%). rFNA yielded a different category 60% of the time. However, 60% remained category I or III. rFNA results of benign or malignant were found in 40% of cases; 1% were SFN/SFM. Twenty-seven percent of patients had surgery after rFNA; of those 68% had category I or III rFNA results. Of all nodules that underwent surgery, 46% were malignant, including 32% with category I rFNA results, and 42% category III. CONCLUSIONS: rFNA for category I and III nodules provided a definitive diagnosis in only 40% of cases, which is important for patient counseling. Malignancy rates at our centre were higher for these categories than predicted by Bethesda. Clinical management should consider institution specific malignancy rates, patient factors, and ultrasound findings.